New species and new records of Plecoptera from Korea and the Russian Far East - Zwick, Peter (Illiesia, 2010)
Plecoptera collected with Malaise traps in South Korea were studied. The material comprised 25 identified species, including seven new species, and sixnew records for Korea. The genus Despaxia (Leuctridae) is recorded from Asia for the first time. The following new species are named: Amphinemura denstigris, Nemoura rugosa, Nemoura tripotini, Despaxia asiatica, Paraleuctra malaisei, Megarcys teslenkonis, and Sweltsa zhiltzovae. Descriptions of several known species are supplemented. Nemoura sahlbergi problematica Zwick, 1973 is considered a nomen dubium. The total number of Plecoptera species known from Korea now equals 57. In addition, Nemoura lazoensis, a new species from the Russian Far East, Primorjski Territory, is described.
Keywords: entomologija; entomology; new species; vrbnice; nove vrste; Plecoptera; Nemouridae; Leuctridae; Capniidae; Perlodidae; Chloroperlidae; South Korea; Russian Far East